Microsoft Cloud Supply Chain & Finance is a finalist in Alexander Hamilton Treasury Awards for its blockchain work - Rhodes, Yorke (2023)
I’m excited to announce that our blockchain work in cloud supply chain has been nominated as a Finalist to claim one of the top 3 spots on the Alexander Hamilton Awards for our work on: “Flexibility, Adaptability, and Risk Reduction Using Blockchain in One of the World's Largest Supply Chains”